Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Compute the series $$1)\space\sum_{n=1}^{\infty}\left(1+\frac{1}{2}+\frac{1}{3}+\cdots+\frac{1}{n+1}\right)\frac{1}{n(n+1)}$$ $$2)\space\sum_{n=1}^{\infty}\left(1-\frac{1}{2}+\frac{1}{3}-\cdots(-1)^{n}\frac{1}{n+1}\right)\frac{1}{n(n+1)}$$

share|cite|improve this question
$1/(n(n+1))=1/n -1/(n+1)$. Have you tried if a lot of terms cancel? – Eckhard Dec 29 '12 at 14:48

3 Answers 3

up vote 3 down vote accepted

In both of these, we will use the telescoping sum $$ \begin{align} \sum_{k=n}^\infty\frac1{k(k+1)} &=\sum_{k=n}^\infty\frac1k-\frac1{k+1}\\ &=\frac1n \end{align} $$

$1)$ Here is one way: $$ \begin{align} \sum_{n=1}^\infty\sum_{k=0}^n\frac1{k+1}\frac1{n(n+1)} &=1+\sum_{n=1}^\infty\sum_{k=1}^n\frac1{k+1}\frac1{n(n+1)}\\ &=1+\sum_{k=1}^\infty\sum_{n=k}^\infty\frac1{k+1}\frac1{n(n+1)}\\ &=1+\sum_{k=1}^\infty\frac1{k+1}\frac1k\\[6pt] &=1+1\\[12pt] &=2 \end{align} $$ $2)$ Here is a similar way:

$$ \begin{align} \sum_{n=1}^\infty\sum_{k=0}^n(-1)^k\frac1{k+1}\frac1{n(n+1)} &=1+\sum_{n=1}^\infty\sum_{k=1}^n(-1)^k\frac1{k+1}\frac1{n(n+1)}\\ &=1+\sum_{k=1}^\infty\sum_{n=k}^\infty(-1)^k\frac1{k+1}\frac1{n(n+1)}\\ &=1+\sum_{k=1}^\infty(-1)^k\frac1{k+1}\frac1k\\ &=1+\sum_{k=1}^\infty(-1)^k\frac1k-\sum_{k=1}^\infty(-1)^k\frac1{k+1}\\ &=1+\sum_{k=1}^\infty(-1)^k\frac1k+\sum_{k=1}^\infty(-1)^{k+1}\frac1{k+1}\\[6pt] &=1-\log(2)+(1-\log(2))\\[12pt] &=2-2\log(2) \end{align} $$

share|cite|improve this answer
thank you for your work. – Chris's sis the artist Dec 30 '12 at 15:57

Hint: Consider the partial fraction expansion of $\frac{1}{n(n+1)}$

share|cite|improve this answer

For the first part, recognize that $\frac {1}{n(n+1)} = \frac {1}{n} - \frac {1}{n+1}$. So the sum can we written as

$$ \sum_{n=1}^{\infty} ( 1 + \frac {1}{2} + \frac {1}{3}+ \ldots + \frac {1}{n+1} ) ( \frac {1}{n} - \frac {1}{n+1}) $$

Break this up into the separate terms of the right parenthesis, and we find that consecutive terms cancel out. Note that we are canceling terms that are directly next to each other, so this step is justified. We'd obtain

$$\sum_{n=1}^{\infty} \big[ (1 + \frac {1}{2} + \ldots + \frac {1}{n+1}) - (1 + \frac {1}{2} + \ldots + \frac {1}{n}) \big] (\frac {1}{n}) = \sum_{n=1}^{\infty} \frac {1}{(n+1)n}$$

Finally, evaluate this as telescoping series $\sum_{n=1}^{\infty} \frac {1}{(n+1)n} = \sum_{i=1}^{\infty} \frac {1}{n} - \frac {1}{n+1} = 1$.

With these ideas, you should try the second part by yourself. At the most, you will need to evaluate $\sum_{n=1}^\infty \frac {(-1)^n}{n+1}$, which you can do by using the MacLaurin expansion $\ln(1+x) = x - \frac {x^2}{2} + \frac {x^3}{3} - \frac {x^4}{4}$ for a suitable value of $x$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.